The Possible Use of Binuangeun White Shirmp (Panaeus monodon Fab) Broodstock as an Alternative to Over Exploited Aceh White Shirmp Broodstock - Etty Riani (Media Konservasi, 2000)
This research was designed to evaluate the biological reproduction aspect of Binuangeun broodstock and also the larval biological aspects and larval qualities. The broodstock were brought to the hatchery of BADP - Labuan Pandeglang. A total of 40 broodstock, 10 female and 10 male from Binuangeun and then 10 female and 10 male from Aceh. Fecundity average from this research from Binuangeunand Aceh was 451.657 and 565.916. The average hatching rate of Binuangeun broodstock was 66,8%, with the average larval survival rate (SR) of nauplii-zoea 63.7%; zoea-mysis 59,8%; mysis-PL1 78,0%; PLI - PL17 80,0% and nauplii - PLI7 23,19%. The average hatching rate (HR) of Aceh broodstock 73,30%; with the average SR of nauplii - zoea 61,7%, zoea - mysis 46,2%, mysis - PLI 77,00/0; PLI - PL17 73,4% and nauplii - PLI7 15,92%. In this research fecundity on the first higher than the second. In this reseach the fecundity rises cause hatching rate decrease, but the hatching rate rises cause the larval survival rate rises too. The quality of broodstock and the larvae of tiger prawn from Binuangen the same as the quality of broodstock and larvae of tiger prawn from Aceh.